Optimizing Moral Education Assistance in the School Community - Lubis, Arbonas; Feri Iswandi Arifin; Iwan Limbong; M. Nail Mughny; Mhd. Adhitya Afriandi; Muhammad Danial; Mhd. Rezha Muji Hafid (As-sunnah: Jurnal Pengabdian Masyarakat, 2024)
The implementation of this research focuses on two objectives, namely, firstly, creating a community that guides children with morals based on the perspective of Islamic religious teachings, and secondly, helping the community in educating the Islamic generation to be able to have morals based on the perspective of Islamic religious teachings to the SD Negeri 07 Brohol community, Sei Suka sub-district, Batubara district. Using the Asset Based Communities Development (ABCD) method by obtaining data through the 5D cycle, namely define (determine) discovery (find), dream (dream), design (design), destiny (do) in order to realize change at each stage with the form of mentoring activities, empowering assets owned by the community with the result that students receive moral and moral learning based on the perspective of Islamic religious teachings, schools understand asset-based development that schools can develop with existing potential and the community increasingly trusts schools that can increase change and develop assets with great potential.